Evaluación técnico-financiera del nuevo tratamiento del agua de inyección para el proyecto de recobro secundario en el campo Moquetá (2019)
The present project was developed thanks to the collaboration of the company Gran Tierra Energy Inc., where information on the injection water treatment plant is collected as a method of secondary recovery of the Campo Moquetá. This is done in order to perform a technical and financial evaluation of the feasibility of the project for the implementation of new equipment and processes for the treatment plant, which provide solutions to the main problems generated by the expiration of the previous environmental license, as they are: content of total suspended solids, content of dissolved oxygen and sulfate-reducing bacteria present in the water. The description of the old water treatment plant was made, as well as the implementation of the new equipment. Subsequently, laboratory tests were performed on untreated water, water treated with the old treatment and water treated with the new treatment. The results of the laboratory tests were compared with each other to verify the efficiency of the implementation of the new water treatment plant.